Pengelolaan Sampah Plastik Dengan Mesin Pencacah di Infrastruktur Industri Pengolahan Sampah Terpadu Asari - Rahayu, Puji; Tutuka, Rachmadi; Pasaribu, Monita; Jerry, Jerry; Ikhsandy, Ferry; Luthfi, Muhammad Zulfikar; Betariani, Khairunisa; Nury, Dennis Farina; Zulkipli, Rohiman Ahmad; Nugroho , Muhammad Erwin Cahyo (Universitas Nahdlatul Ulama Sumatera Utara, 2025)
The increasing problem of plastic waste has become one of the biggest environmental challenges in the world today. To overcome this problem, the development of plastic shredding technology is an effective solution to support the plastic recycling process. This study aims to design and develop an efficient and environmentally friendly plastic waste shredding machine, which is able to reduce the volume of plastic waste and facilitate the recycling process. The research methodology includes identifying user needs, literature studies, developing design concepts, detailed design using software, prototyping, and testing and evaluating machine performance. The designed shredding machine has a shredding capacity of 50 kg/hour with lower energy consumption compared to existing commercial shredding machines. Consistent machine testing in producing plastic flakes with uniform sizes, which are suitable for further recycling processes. Performance analysis relates to machines that are able to process various types of plastic, including PET, HDPE, and PP, with high shredding efficiency. The developed plastic shredding machine is able to provide a practical solution for plastic waste management by optimizing the recycling process and reducing negative impacts on the environment. The development of this plastic shredding machine is expected to contribute significantly to efforts to reduce plastic waste and support environmental sustainability.